Analisis Faktor-faktor Penyebab Turnover Karyawan pada Toko Top Mode Makassar Sulawesi Selatan - Bendan, Chelsy Julia Yohanis; Sambara, Kordiana; Rasinan, Djusniati (YASIN, 2025)
The ability to read the Qur'an of students in Islamic universities is still a Employee turnover is a common phenomenon in the business world, especially in the retail sector. High turnover rates can have a negative impact on operational efficiency, recruitment costs, and employee motivation. This study aims to analyze the factors that influence employee turnover at Toko Top Mode, Makassar. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and literature studies conducted in January 2025. Research informants consisted of managers and employees in various divisions. The results of the study indicate that employee turnover at Toko Top Mode is influenced by several main factors, namely lack of career development opportunities, less supportive work environment, uncompetitive compensation and benefits, and imbalance between work and personal life. These factors cause job dissatisfaction, which encourages employees to seek opportunities elsewhere. These findings are expected to provide insight for management in developing better human resource policies to reduce turnover rates and increase workforce stability in the retail industry.